(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Safe’I R, Latumahina FS, Dewi BS, Ardiansyah F. 2021. Short Communication: Assessing the state and change of forest health of the proposed arboretum in Wan Abdul Rachman Grand Forest Park, Lampung, Indonesia. Biodiversitas 22: 2072-2077. Forest health is the fundamental of sustainable forest management. As such, forest health needs to be continually monitored and maintained. This study assessed the state and change of forest health of the prospective arboretum in Wan Abdul Rachman Grand Forest Park (Tahura WAR), Lampung, Indonesia, aiming that the arboretum can serve for integrated conservation and education forest (Tahura War). This research used the Forest Health Monitoring (FHM) method by combining the parameters of vitality (i.e., tree damage and tree crown condition) and biodiversity (tree species diversity) across four Forest Health Monitoring plot clusters. The results showed there was a change in the state of forest health of the prospective arboretum in Tahura WAR. The first measurement showed that 50% of plot clusters had a status of bad, while 25% was moderate and 25% was good. The results of the second measurement showed that 50% of plot clusters had a status of moderate, while 25% was bad and 25% was good. This finding suggests that the prospective arboretum experienced changes toward better conditions in health status. Even so, it is still necessary to carry out regular forest health monitoring activities to determine trends.